Pengembangan Usaha Mikro Kecil dan Menengah (UMKM) dengan Program Pemasaran Desa Jambu Raya di Desa Jambu, Kabupaten Sumedang - Alifah Fidela; Aprinaldi Pratama; Tita Nursyamsiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Micro, small and medium enterprises (MSME) are proving to contribute to the Indonesian economy. SMEs play an important role in national development, i.e. labor absorption, equity equality, rural economic development, non-oil exports, and the increase of gross domestic product (GDP). The problems often experienced by SMEs are the limitation of working capital, the capacity of human resources is very low and Minimnnya mastery of science and technology that generally affects the prospect of unclear business. Therefore, the socialization of SMEs is given that the business is able to survive in the market and develop better by paying attention to product, place, promotion, and price of the products offered. Keywords: capital, gross domestic product, micro small and medium enterprises, resources